Comparing trends in esophageal adenocarcinoma incidence and lifestyle factors between the United States, spain, and the Netherlands - Kroep, S.; Lansdorp_Vogelaar, Iris; Rubenstein, J.; Lemmens, V.; Van Heijningen, E.; Aragonés, N.; Van Ballegooijen, M.; Inadomi, J. (Nature Publishing Group, 2014)
Objectives: The incidence of esophageal adenocarcinoma (EAC) in the western world has been rapidly increasing. The trends in obesity and other lifestyle-associated factors have been hypothesized to be important drivers of this increase. We tested this hypothesis by comparing changes in these factors with changes in EAC incidence over time between three western countries. Methods: Data on EAC incidence trends were abstracted from the SEER-9 registry (1975-2009) for the United States, from multiple cancer registries (1980-2004) in Spain, and from Eindhoven Cancer Registry in the Netherlands (1974-2010). In addition, we collected trend data on obesity, smoking, and alcohol consumption. The trend data were analyzed using log-linear regression. RESULTS: In 1980, the EAC incidence was similar among the three countries ((0.46-0.63) per 100,000). EAC incidence increased in all, with the largest increase observed in the Netherlands, followed by the United States and Spain (estimated annual percentage of change=9.7%, 7.4%, 4.3%, respectively). However, this pattern was not observed in lifestyle factors associated with EAC. With regards to obesity, the United States clearly has had the highest prevalence rates both in the past and in the present. For alcohol, the highest consumption rates are seen in Spain. Smoking showed a reverse trend compared with EAC among all three countries in the last 20 years. Conclusions: International trends in EAC incidence do not match corresponding trends in lifestyle-associated factors including obesity. Our findings suggest that factors other than obesity must be the important drivers for the increase in EAC incidence.